Coordinate initiation of Drosophila development by regulated polyadenylation of maternal messenger RNAs. - Salles, F.J.; Lieberfarb, M.E.; Wreden, C.; Gergen, J.P.; Strickland, S. (Science, 1994)
Pattern formation in Drosophila depends initially on the translational activation of maternal messenger RNAs (mRNAs) whose protein products determine cell fate. Three mRNAs that dictate anterior, dorsoventral, and terminal specification--bicoid, Toll, and torso, respectively--showed increases in polyadenylate [poly(A)] tail length concomitant with translation. In contrast, posteriorly localized nanos mRNA, although also translationally activated, was not regulated by poly(A) status. These results implicate at least two mechanisms of mRNA activation in flies. Studies with bicoid mRNA showed that cytoplasmic polyadenylation is necessary for translation, establishing this pathway as essential for embryogenesis. Combined, these experiments identify a regulatory pathway that can coordinate initiation of maternal pattern formation systems in Drosophila.